They All Had a Reason - Leathers, Michele ([United States] : EMAR Publishing, 2021)
"Sixteen-year-old Charlotte is convinced her life would be perfect if she could only get past the one obstacle holding her back: A girl named Bellany Silverfield, who seems to have it all -- beauty, popularity, power and the boy of Charlotte s dreams. But when Bellany is murdered, Charlotte s life doesnt get any better. In fact, it gets much worse. Charlotte worries that circumstantial evidence and rumors of motive will make her a prime suspect. Shes forced to question the loyalty of her closest friends and to place her trust in a boy she barely knows. But one of these people is definitely lying to her." -- Amazon.
Keywords: Teenage girls -- Fiction; Secrecy -- Fiction; Murder -- Fiction; Teenage girls -- Fiction; Secrecy -- Fiction; Murder -- Fiction; Detective and mystery fiction